2012
DOI: 10.1007/s12020-012-9745-5
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba L. extract enhances the effectiveness of syngeneic bone marrow mesenchymal stem cells in lowering blood glucose levels and reversing oxidative stress

Abstract: Bone marrow mesenchymal stem cells (BMSCs) are potential therapy for diabetes. Owing to the oxidative stress caused by hyperglycemia, these transplanted BMSCs are with high rate of apoptotic death after transplantation. Ginkgo biloba L. extract (EGB) is a potent antioxidant which can remove free radicals. The study was to investigate whether EGB can protect BMSCs from oxidative stress in vitro and enhance the efficacy of BMSCs in lowering blood glucose levels after transplantation. BMSCs were cultured with H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…More studies [ 9 ] confirmed the hypoglycemic effect of EGb. Daye Cheng et al [ 10 ] administered streptozotocin-induced diabetic rats with high, medium, and low doses of EGb.…”
Section: Ginkgo Bilobamentioning
confidence: 87%
“…More studies [ 9 ] confirmed the hypoglycemic effect of EGb. Daye Cheng et al [ 10 ] administered streptozotocin-induced diabetic rats with high, medium, and low doses of EGb.…”
Section: Ginkgo Bilobamentioning
confidence: 87%
“…Tumor growth is closely associated with ROS production which is also a underlying mechanism of tumor growth, we measured the level of MDA and activities of SOD in the serum. The measurement of serum MDA and SOD was described in detail in Ren et al [13] in each mouse in the four treatment groups and in the untreated control mice.…”
Section: Determination Of Malondialdehyde (Mda) and Superoxide Dismutmentioning
confidence: 99%
“…To reveal the mechanisms underlying GBE and CTX inhibiting the growth of EMT-6 cells, we determined the expression of key elements in the NF-κB signaling pathway, PI3K/AKT pathway and apoptosis. Western blot analysis was conducted as in the protocols described in Ren et al [13].…”
Section: Western Blotmentioning
confidence: 99%
“…Ginkgo biloba L. extract (EGB) is a traditional herbal medicine that can remove free radicals. EGB is well known for its antioxidant and antiinflammatory activities (Ren et al, 2013). Previous studies showed that EGB may have antitumor effects that are related to its antioxidant, antiangiogenic, and gene-regulatory actions (Dias et al, 2013;Park et al, 2013;Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%